Servant Leadership, Motivation, and School Culture as Predictors of Teacher Discipline - Pujianti, Ninit; Nellitawati, Nellitawati; Damanik, Enceria; Ningrum, Tia Ayu (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
Teacher discipline supports reliable instructional delivery, yet public elementary schools in Solok City continue to face problems involving punctuality, classroom presence, administrative completion, and compliance with professional duties. This study examined servant leadership, teacher motivation, and school culture as predictors of teacher discipline. A quantitative cross-sectional survey involved 221 teachers selected proportionally from 41 schools. Data were collected through four five-point Likert instruments containing 160 valid items. Reliability was strong, with Cronbach’s alpha values from .907 to .969. Separate regressions showed that servant leadership (β = .466), motivation (β = .613), and school culture (β = .289) each positively predicted discipline (p < .001). The combined model was significant, F(3, 217) = 51.893, p < .001, and explained 41.8% of the variance. Motivation remained the strongest positive predictor, followed by servant leadership, whereas school culture produced a negative partial coefficient after shared variance was controlled. The study offers an integrated model for teacher discipline in Indonesian primary education and indicates that school-culture effects require further mediation or multilevel analysis